Optimalisasi Potensi Keterampilan Usaha Kecil melalui Literasi Keuangan: Inisiatif Pengabdian Masyarakat oleh Spesialis Area Daya BTPN Syariah di Kabupaten Jombang - Octavia Angelita, Debry; Ika Kusuma Wardhani, Nuruni (PADMA, 2024)
This research aims to increase the potential skills of small businesses through financial literacy. This research develops and applies a financial education model based on basic financial technology. This model is designed to help small businesses understand and manage their finances effectively. This research was carried out by holding financial material training and implementation for small business actors. This training covers basic financial material, financial management, and the use of financial technology to increase financial literacy. The research results show that small business actors who take part in financial training have a significant increase in financial skills. They can better manage their finances, and have the ability to deal with financial crises. In synthesis, this research shows that the development and application of a financial education model based on financial technology can help increase the potential skills of small businesses. The results of this research can be used as a reference for organizations and individuals who want to improve their small business skills